Raspberries - Funt, Richard C (CABI, 2014)
This book is dedicated to the amazing collection of researchers, growers and marketers, who during the 19th and 20th centuries brought the raspberry to millions of people around the world, and to those present and future generations who continue to improve the raspberry plant, create cost-ef ective production systems to improve the harvest and marketing of the raspberry, and continually learn how the raspberry can improve human health in the 21st century. Speciﬁ cally, we are indebted to plant breeders, plant pathologists, virologists, entomologists, plant scientists, agricultural economists, agri- cultural engineers, researchers, outreach specialists, agricultural editors and to many others who have spent lifetimes working to improve raspberry cultivars and grow the raspberry industry worldwide. Passionate people have produced nursery plants, conducted ﬁ eld trials, tested and sought chemical registration for use on this minor fruit crop. Many graduate students have contributed ﬁ eld and medical research projects and published their results in scientiﬁ c publications and bulletins. Agricultural engineers improved drip irrigation by using ultraviolet- resistant material, created uniform distribution of water over long distances and hilly terrain, and developed daily watering schedules to optimize yields. They improved the ef ectiveness and ei ciency of pesticide application equipment as well as raspberry mechanical harvesters that can reduce the need for hand harvesting, and they have designed and built polythene tunnels for year-round production and sustained fruit quality, in spite of the vagaries of weather and climate variations.